A Tale of Two Elements: Effects of Foliar Nitrogen and Phosphorus Stoichiometry on Plant-Insect Interactions - Tao, Leiling; University of Michigan. Library. Deep Blue. (2013)
fertilization. Finally, I explored feedback between herbivore activity and nutrient allocation in plants. I showed that herbivores can exert top-down effects on plant nutrient concentration by changing plant resource allocation patterns. Specifically, when under simultaneous attack by above- and belowground herbivores, A. syriaca was able to allocate newly absorbed N to stems and render it unavailable to future attack by both herbivores. Such nutrient reallocation may represent an important mechanism by which plants tolerate herbivore attack.
ratios than those of the plants, suggesting that the N demand of the aphid always exceeds P demand, even under high N levels. Additionally, P fertilization increased the production of latex in milkweed, which is a defense trait that negatively affected D. plexippus growth rate. In Chapter 3, I found that although foliar N concentration in A. syriaca was positively correlated with the growth rate of D. plexippus, this relationship disappeared when caterpillars fed on A. incarnata, and became negative when fed on A. curassavica. The mechanism for the negative relationship was because per unit toxicity of cardenolide was higher at high foliar N levels. Because monarchs sequester cardenolides from milkweeds as defense, the increased toxicity under high N could influence sequestration efficiency. Indeed, in chapter 4, I found that the efficiency with which D. plexippus sequesters cardenolides from milkweed was reduced by soil
The growth, survival, defense and reproduction of herbivores are influenced by plant nutrient concentrations. I integrated nutritional ecology with principles of ecological stoichiomtery and chemical ecology to explore the effects of plant quality on insect herbivores. Although nitrogen (N) is considered to be the major limiting nutrient for terrestrial insect herbivores, evidence suggests that the stoichiometric balance between N and phosphorus (P) may be equally important. In Chapter 2, I explored potential P limitation in the monarch caterpillar Danaus plexippus and an aphid Aphis asclepiadis, which are specialist insects feeding on milkweeds (Asclepias). I found that although the host plant, A. syriaca was co-limited by soil N and P, neither of the two insect species experienced induced P limitation. The body tissues of A. asclepiadis always exhibited higher N: P
Dissertation (Ph.D.)--University of Michigan.
Includes bibliographical references.
Mode of access: Internet.
Keywords: Plant-insect interactions; Ecological stoichiometry; Chemical ecology; Nitrogen deposition